Perancangan Sistem Informasi Registrasi KK Dan KTP Berbasis Web Di Kecamatan Kiaracondong Bandung - Emalia, Lilis; Yanuar, Yudhi; Maryam, M (STIKOM Tunas Bangsa Pematangsiantar, 2023)
This research is aimed to find out the design of registrative information system KK and KTP using PHP and MySql in Kecamatan Kiaracondong, Bandung, which is intended for facilitating the process of registration services to the population. In data collection, the author used method of observation, interviews, and literature study, and for research the author used the method of qualitative and for software development method was used Waterfall method. The current system is still using manual system, therefore some problems arise such as difficult to find data and loss of data at any time in the registrative process. The use of information systems facilitates the completion of each job, hence this information system can be useful in the agency in handling its duties and in handling the registrative activities of population services.